Decision support for the evaluation of building life cycle effectiveness - Banaitiene, Nerija; Turskis, Zenonas (Technological and Economic Development of Economy, 2004)
This paper presents a multiple criteria decision model for the life cycle of single family houses analysis based on a decision support system. Methods of multiple criteria analysis are applied for a complex analysis of the single‐family houses life cycle as well as for the evaluation of decisions. The method of multivariant design is applied for making variants of the life cycle of single‐family houses. The multivariant design and multiple criteria evaluation of a building life cycle allow the interested parties (client, contractor, user, etc.) to make efficient decisions on the ground of a quantitative and qualitative variants analysis. The decision maker's attitude can be reflected in the analysis process by the weighting of criteria. The proposed methodology provides a useful tool for building life cycle evaluation. Having applied the information gathered in the database, using the models of a model base, various interested parties of a building life cycle are able to make effective decisions. The system provides a user with all the necessary support required for decision making: in information terms the receipt of quantitative and conceptual information describing a building life cycle, gathering and use thereof, in terms of evaluation the analysis of such information applying the methods of a multiple criteria analysis.Article in Lithuanian.Sprendimų parama vertinant pastato gyvavimo proceso efektyvumąFirst Published Online: 21 Oct 2010